Patellar Tendon Allograft Reconstruction - Matthew G. Spivey MD; Michael P. Campbell MD; Lee G. Gammon MD; Alexander R. Vap MD (SAGE Publishing, 2021)
Background: Chronic patellar tendon injuries can cause significant functional deficits due to anterior knee pain, extension weakness, and extensor lag. With chronic injuries, the tissue is inadequate and of poor quality. Chronic injuries require autograft or allograft for augmentation or reconstruction. We present reconstruction of a chronic patellar tendon injury with Achilles tendon allograft. Indications: Chronic patellar tendon injuries causing functional deficits, including knee extension weakness, extensor lag, and anterior knee pain. Technique Description: A longitudinal incision is made over the patellar tendon, and the patellar tendon is excised. Two guide pins are drilled in a retrograde fashion through the patella and are overdrilled with a reamer. A trough is made at the tibial tubercle using an oscillating saw. The Achilles allograft calcaneal bone block is contoured to the appropriate size, and then press fit into the trough. Two 4.0-mm fully threaded cannulated screws with washers are used to secure the bone block. The fresh frozen Achilles allograft is doubled over, and a double Krackow running locking suture is placed. A V-Y advancement of the quadriceps tendon is performed to ensure adequate advancement of the patella. The limbs of the Krackow suture are pulled through the patella drill holes and tied with knee in full extension. Results: At 1 year, patients can expect near full range of motion with minimal extensor lag. Reconstruction results in improved pain and function as compared with preoperatively, as well as return to activities. Conclusion: Achilles tendon allograft is a good option for reconstructing chronic patellar tendon injuries. Advantages of the Achilles allograft include the bone-to-bone healing at the tibia, lack of donor site morbidity, and the large amount of tissue available for reconstruction.